Preparation of Tb³⁺-doped K₂GdF₅ Used to Neutron Dosimetry - Ha , Xuan Vinh; Doan , Phan Thao Tien; Nguyen , Chi Thang (Nuclear Science and Technology, 2014)
The neutron absorption section of gadolinium atom is very high, so that the K2GdF5 crystals doped with Tb3+ ions have been studied for neutron dosimetry by the thermoluminescence (TL) method. The K2GdF5 crystals doped 2%, 3% and 5% concentrations of Tb3+ ions were synthesized by solid state reaction method. The TL properties were studied after the exposure of the samples to neutron source. The experimental results showed that the TL glow-curves of K2GdF5:Tb3+ has the simple, suitable shape for the dosimetry applications. The TL sensitivity of this material is higher than that of commercial TLD-100 and TLD-900 dosimeters. The thermal fading effect of Tb3+-doped K2GdF5 is very low. The glow curve consists of the main peak at temperature of 202oC. The glow curve deconvolution into individual the peaks showed that the curve had a main peak at 202oC, and kinetic order b = 2. The study results indicated that the K2GdF5 doped with Tb3+ is very remarkable material can be applied in neutron dosimetry field.